Family Language Policies of Vietnamese–Australian Families - Tran, Van H.; Verdon, Sarah; McLeod, Sharynne; Wang, Cen (Journal of Child Science, 2022)
This study aimed to investigate reported family language policies (quy tắc sử dụng ngôn ngữ cho gia đình) and language maintenance practices among Vietnamese–Australian parents. This mixed-methods study collected 151 Vietnamese–Australian parents' responses to close- and open-ended questions within an online questionnaire that was available both in English and Vietnamese. Bivariate analyses and logistic regression were conducted to explore associations between family language policies and factors related to demographics and Spolsky's language policy theory. Content analysis was undertaken in NVivo to investigate family language policies. One-third of the participants (35.6%) reported to have a family language policy and 72.5% of those with a policy indicated that they consistently implemented their policy. Significant factors associated with having a family language policy were parents' higher Vietnamese proficiency, more Vietnamese language use with their children, and intention of future residence in Vietnam. The four identified language policies were as follows: (1) using Vietnamese with the nuclear family (FLP1), (2) Vietnamese outside the nuclear family (FLP2), (3) English at home (FLP3), and (4) English outside the home (FLP4). Some families used more than one of these concurrently. This is one of the first large-scale mixed-method studies to explore family language policies, and the first to explore this issue with Vietnamese-speaking families in Australia. Many Vietnamese–Australian families do not explicitly have a family language policy aimed at maintaining Vietnamese at home; therefore, the Vietnamese–Australian community is at risk of a shift toward English language dominance and home language loss. As a result, the benefits of multilingualism within the Vietnamese–Australian community may be lost without support from the government and community to maintain their home language.
Keywords: language policy; Spolsky's language; demographics; Vietnamese–Australian parents